2015
DOI: 10.1007/s00467-015-3101-y
|View full text |Cite
|
Sign up to set email alerts
|

An atypical case of acute kidney injury: Questions

Abstract: CaseA previously healthy 9-month-old boy presented to the hospital with a 10-day history of decreased energy, feeding difficulties, maculopapular rash, vomiting, and fever. He had been diagnosed with pneumonia and started on oral amoxicillin 2 days before hospital admission. On physical examination, he had a rectal temperature of 38.5°C, a pulse of 134 beats per minute, and a blood pressure of 118/69 mmHg. He had mild intercostal retractions with abdominal breathing and decreased air entry at the left base. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…An onset of complement deficiency, pneumococcal infection, abnormal metabolism of cobalamin, and so on can lead to atypical hemolytic uremic syndrome (aHUS), which is related to genetic mutations and has a distinct pathophysiology. [ 3 , 6 , 7 ] So far, only a few cases of HUS have been triggered by a metabolic disease, such as diabetes mellitus [ 8 , 9 ] and metabolic disorder of cobalamin. [ 10 , 11 ] Recently, Adrovic et al described a case of a 6-year-old girl with CblC disorder, who was found to have a homozygous mutation in exon 4 of MMACHC, c. 484G >T. [ 11 ] Although the serum level of VitB12 was normal in the patient, the bone marrow showed an obvious degeneration, so we highly suspected that it was caused by metabolic abnormalities of cobalamin.…”
Section: Discussionmentioning
confidence: 99%
“…An onset of complement deficiency, pneumococcal infection, abnormal metabolism of cobalamin, and so on can lead to atypical hemolytic uremic syndrome (aHUS), which is related to genetic mutations and has a distinct pathophysiology. [ 3 , 6 , 7 ] So far, only a few cases of HUS have been triggered by a metabolic disease, such as diabetes mellitus [ 8 , 9 ] and metabolic disorder of cobalamin. [ 10 , 11 ] Recently, Adrovic et al described a case of a 6-year-old girl with CblC disorder, who was found to have a homozygous mutation in exon 4 of MMACHC, c. 484G >T. [ 11 ] Although the serum level of VitB12 was normal in the patient, the bone marrow showed an obvious degeneration, so we highly suspected that it was caused by metabolic abnormalities of cobalamin.…”
Section: Discussionmentioning
confidence: 99%